IMPLEMENTASI KONTROL PROPORSIONAL, INTEGRAL DAN DERIVATIF (PID) TERHADAP KECEPATAN MOTOR DC - Andi Fatmawati, Mery Subito, Baso Mukhlis (Foristek, 2018)
Recently, research on DC motor has been rapidly developed, from the wether simple until the advanced / complicated . DC motor utilizes DC power connected to its armature and field (stator) winding, in which the power will be converted to mechanical energy. In addition, DC motor has beneficial in big initial torgue and simple velocity control. When DC motor given the burden of arbitrary, rotation speed of motor also change.PID method was employed to control the rotation speed remaining constant. Implementation and simulation method was proposed in this research. The result shows that when 12,5 V of voltage was applied to DC Motor, at no load – open loop, the rotation speed was 2000 rpm. Increasing load up to 0,5 N.m, decreased the rotation from 2000 rpm to 1404 rpm. Furthermore, for closed loop using Proportional control (P), Proportional Integral (PI) and Proportional Derivatif (PD) control. proved that rotation of motor was unstable. Whereas, PID control method can stabilize the rotation of motor and give just response,reacling steady state at 3,4 s with 0,004 V of error.